The socio-economic background of the students of Pura Academy implications for curriculum development and school administration - Tabing, Apolinario A. 1920- (s.n.], 1972)
Educators know very little about the socio-economic background of their student and as a result the schools have been charged of being irrelevant. The present study sought to determine the socio-economic background of the students of Pura Academy and to propose improvements in the curriculum and